Junior high school students' perceptions of physical education subjects: An instrument development - Mu’arifin (UIR Press, 2021)
Students' perception of the concept of physical education is one of the determinants of success in learning. Physical activity characteristics that are dominated by physical activity are often perceived as inaccurate, resulting in a low appreciation of it. This study aimed to develop an instrument to measure students' perceptions of the concept of physical education. This research is development research involving 693 junior high school students in Pacitan, Tulungagung, and Kediri districts. To measure the validity of the instrument, the biserial point correlation technique was used with the help of Microsoft Excel, and to measure the reliability of the instrument used the Cronbach Alpha analysis technique with the help of SPSS version 23. The results obtained were the compilation of 71 statements that could be used to measure students' perceptions of the concept of physical education. Teachers can use the results of this development to measure perceptions, especially junior high school students, about the concept of physical education subjects so that teachers can prepare learning materials based on the perception data obtained. This development research only measures perceptions at the junior high school level, it is hoped that further research can involve motivation and implementation of physical education learning at various levels of education.